1999
DOI: 10.1002/(sici)1097-4652(199912)181:3<479::aid-jcp12>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of expression of collagenase-3 in normal, differentiating rat osteoblasts

Abstract: We investigated the regulation of collagenase-3 expression in normal, differentiating rat osteoblasts. Fetal rat calvarial cell cultures showed an increase in alkaline phosphatase activity reaching maximal levels between 7-14 days post-confluence, then declining with the onset of mineralization. Collagenase-3 mRNA was just detectable after proliferation ceased at day 7, increased up to day 21, and declined at later ages. Postconfluent cells maintained in non-mineralizing medium expressed collagenase-3 but did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 57 publications
3
27
1
1
Order By: Relevance
“…Located Upstream of the TSS-Mmp13 transcription is up-regulated during early precursor cell differentiation into mature, mineralizing osteoblasts (14) and modulated by a myriad of regulatory factors that include 1,25(OH) 2 D 3 (23). These conclusions are confirmed by the observations in Fig.…”
Section: Mmp13 Is Regulated By Three Distinct Distal Enhancerssupporting
confidence: 66%
See 1 more Smart Citation
“…Located Upstream of the TSS-Mmp13 transcription is up-regulated during early precursor cell differentiation into mature, mineralizing osteoblasts (14) and modulated by a myriad of regulatory factors that include 1,25(OH) 2 D 3 (23). These conclusions are confirmed by the observations in Fig.…”
Section: Mmp13 Is Regulated By Three Distinct Distal Enhancerssupporting
confidence: 66%
“…In studies of PTH action, Mmp13 was found to be regulated by Runt-related transcription factor-2 (RUNX2) through a Runt binding domain DNA sequence located near an AP-1 site adjacent to the Mmp13 promoter (9). Additional studies revealed that both PKC and PKA signaling pathways are active at the AP-1 and RUNX2 binding sites, respectively (14,15). This ongoing work has focused much of the molecular investigation of Mmp13 regulation by PTH and other hormones on these specific promoter proximal sites in bone cells.…”
mentioning
confidence: 99%
“…In bone formation, mineral deposition occurs in the final stage of osteoblast differentiation and is associated with maximal osteoblastic expression of osteocalcin and MMP-13 (20,21,53). Several in vitro studies have indicated that the clonal cell line, C2C12, when cultured under appropriate conditions, might give rise to cells of the osteoblastic lineage with the addition of BMP-2 (50).…”
Section: Discussionmentioning
confidence: 99%
“…Various bone-resorbing agents, such as PTH, increase collagen degradation by increasing MMP production and inhibiting collagen synthesis (19). Similar to osteocalcin, MMP-13 gene expression increases during osteoblastic differentiation (20,21) and is transcriptionally regulated by Runx2, a runt domain-binding transcription factor found in osteoblasts, during this process.…”
Section: Introductionmentioning
confidence: 99%
“…For example, PTH stimulates collagenase-3 gene expression in osteoblastic cells and requires the activator protein-1 (AP-1) and RD binding regions found just upstream of the collagenase-3 transcriptional start site (52,53). Similar to OC, collagenase-3 gene expression increases during differentiation (6,54) and is transcriptionally regulated during this process (6). Given that collagenase-3 and OC are expressed during similar periods of osteoblast differentiation and that expression of both genes is regulated by RUNX2/Cbfa1, it seems reasonable to hypothesize that collagenase-3, like OC, is also regulated by integrin interaction with the extracellular matrix.…”
mentioning
confidence: 99%